Improved Electromagnetic Interference Shielding Properties Through the Use of Segregate Carbon Nanotube Networks - Park, Sung-Hoon (Materials (Basel), 2019)
We report the enhanced electromagnetic interference (EMI) shielding properties of hybrid carbon nanotube (CNT) composites consisting of more than two kinds of fillers through the use of segregate conducting networks. An excluded volume was created by micro-sized silica particles that concentrate the CNT network, resulting in improved electrical conductivity and microwave properties. To achieve the optimal dispersion of CNTs and silica particles, high shear force was applied to the pre-cured composite mixture via three-roll milling. Depending on the micro-silica content ratio, we observed improved electrical conductivity and EMI shielding properties. For a quantitative comparison to observe the excluded-volume effects, a CNT composite without micro-silica was measured in parallel with the other sample.